2005
DOI: 10.1128/iai.73.10.6923-6934.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of HtrA in Surface Protein Expression and Biofilm Formation by Streptococcus mutans

Abstract: The HtrA surface protease in gram-positive bacteria is involved in the processing and maturation of extracellular proteins and degradation of abnormal or misfolded proteins. Inactivation of htrA has been shown to affect the tolerance to thermal and environmental stress and to reduce virulence. We found that inactivation of Streptococcus mutans htrA by gene-replacement also resulted in a reduced ability to withstand exposure to low and high temperatures, low pH, and oxidative and DNA damaging agents. The htrA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 86 publications
1
78
0
Order By: Relevance
“…A Kan-resistant cassette with flanking modified loxP sites was amplified from pUC4 ⍀Kan (39) using the primers lox71-Km-F and lox66-Km-R (for all primers, see Table 2) and cloned into EcoRV-digested pIB-D48 to generate pIB-D50. Plasmid pIB-D50 was lin- pIB104::Em earized with EcoRI and transformed into S. mutans UA159 as previously described (9). The transformants were selected on THY plates containing Kan; one such transformant was selected and named IBS-D20.…”
Section: Methodsmentioning
confidence: 99%
“…A Kan-resistant cassette with flanking modified loxP sites was amplified from pUC4 ⍀Kan (39) using the primers lox71-Km-F and lox66-Km-R (for all primers, see Table 2) and cloned into EcoRV-digested pIB-D48 to generate pIB-D50. Plasmid pIB-D50 was lin- pIB104::Em earized with EcoRI and transformed into S. mutans UA159 as previously described (9). The transformants were selected on THY plates containing Kan; one such transformant was selected and named IBS-D20.…”
Section: Methodsmentioning
confidence: 99%
“…An investigation by Biswas & Biswas (2005) found that deletion of the HtrA extracellular protease/chaperone resulted in increased levels of extracellular GAPDH in culture media. It is not known how GAPDH or other cytoplasmic proteins are transported, as they do not contain signal peptides.…”
Section: Extracellular Gapdh Activity Is Increased In Yidc Mutantsmentioning
confidence: 99%
“…A study by Biswas & Biswas (2005) investigated the effects of deletion of the HtrA extracellular protease/chaperone and found that levels of extracellular GAPDH in culture media increased when HtrA was absent. Extracellular GAPDH activity was increased in both DyidC1 and DyidC2 mutants compared with the parental strain, with a greater effect seen with DyidC2.…”
Section: Group (Strain)mentioning
confidence: 99%
“…In consistency, htrA mutants of many pathogens show attenuated virulence [128][129][130][131]. Intriguingly, a novel role has recently been identified for HtrA of Helicobacter pylori and Campylobacter jejuni: HtrA was found to be secreted during infection and acts as a virulence factor that specifically cleaves the extracellular domain of E-cadherin on infected gastric epithelial cells [132][133][134][135].…”
Section: Thermo-regulated Disassembly Of Oligomeric Protein Sensorsmentioning
confidence: 99%